Desenvolvimento de uma metodologia para a coordenação hidrotérmica de longo prazo em mercado elétrico competitivo - Paredes, Romel Wiliams Jimenez (2007)
In this work a methodology based on linear programming for long-term hydrothermal scheduling of electric power systems is proposed. The objective of the hydrothermal scheduling is to find an optimal operation for a specific time interval and with high reliability and minimum cost. That is equivalent to determine an optimal generation scheduling for the power plants and for each time interval considered, in order to the power system satisfies the forecasted demand. Linear models of the power system components are adopted, and with the option to solve systems with multiple reservoirs and buses. It was implemented a computer program using MATLAB platform for application to small test power systems and configurations of real-size systems such as the interconnected Peruvian System and the Brazilian South-Souheast System. For the solution of the linear optimization problem was used the interior points method. From the analysis of the test systems results is concluded that the linear model may capture adequately the relevant characteristics of the real power system and it may be eficient and precise such as the detailed model.